Beam Steerable Antenna Development for Wireless Health Monitoring - Rabbani, Muhammad Saqib; Feresidis, Alexandros (2019 UK/ China Emerging Technologies (UCET), 2019)
A wideband high gain (>20dBi) beam scanning microstrip antenna array is presented for remote vital sign monitoring utilizing Doppler radar technique at 60 GHz-band. The array is designed by 32 (8×4) extended size patch elements where 8 elements are fed in series in four columns. Beam scanning is achieved by tuning the operating frequency across 58-63 GHz operating frequency band. Since a narrow frequency band is required for Doppler radar in vital sign monitoring, the beam scanning property is employed to detect vital signs of a person changing locations to different angular positions. Remote health monitoring measurements are taken with two identical antennas at 1-2 m distance from the subject. It is shown that both the breathing rate (BR) and heartbeat rate (HR) can be successfully detected within 20° of the angular range by tuning the operating frequency from 58-63 GHz.